A busca por um ambiente em que todos espaireçam: a administração pública na perspectiva de fragmentos da gestão ambiental em Goiânia (1933-1959) - Elias de Paula, Thiarlles (2017)
This paper aims to understand, from a perspective of fragments of what is called environmental management (or of space), part of the public administration in Goiânia between the years of 1933 to 1959. It addresses the control of public power in the city by as a means of prophylactic, sanitary, zoning, landscaping and urbanism justifications, because at the time studied, the term environment was not used, however, the areas to be administered were already conceptualized in the environment. However, many administrative actions of the urban space addressed at the time, would be used until the present day, but not within a taxonomy related to the synergic and cumulative impacts for the context of the studied period. In this perspective, the concept of the environment of Goiania is based on lexical resignigned, with the look in the past, from an environmental perspective. The following basic items of environmental (or environmental) management, considered most important in the period, are considered: solid waste (garbage collection), water uses, urban zoning and land use. landscaping and urban planning. These are not addressed in a segregated way, but observing their synergistic and cumulative effects that would form an environment for the residents of Goiânia to "get away". Primary sources are used, which are administrative acts, such as memos, letters, reports, among other documents issued by the public authority at the time. This, to analyze the actions of the public administration in Goiânia.